Legit check! Assessing the influence of linguistic cues in online reviews on consumers' purchase intention with the mediating role of perceived authenticity - Dela Merced, Norman Daniel Miguel (Animo Repository, 2021)
E-commerce has revolutionized the way consumers shop for goods and services, and there have been recent drastic developments in the industry due to the COVID-19 pandemic. However, the way online reviews are crafted has also evolved with the changing landscape of online shopping–making more online consumers prone to falling victim to fake online reviews. With limited face-to-face interactions in making online purchases, consumers can only judge the authenticity of reviews with linguistic cues. Given this, the study aims to assess the mediating role of the perceived authenticity of online reviews on the relationship between the linguistic cues of perceived comprehensibility, perceived specificity, perceived exaggeration, and perceived tentativeness, and consumer purchase intention. The results from 400 respondents revealed that perceived authenticity partially mediates the relationship between perceived comprehensibility, specificity, and tentativeness and purchase intention, while it completely mediates the relationship between perceived exaggeration and purchase intention. Key recommendations for online consumers, managers of e-commerce platforms, designers of online review sites, the government, and future researchers were also provided in light of the research findings.